DEVELOPMENT OF INCLUSIVE EDUCATION IN THE REPUBLIC OF UZBEKISTAN: INCLUSION OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN INCLUSIVE ENVIROMENT- PRESETT - Agzamxodjayeva Saodatxon Abrarovna (Western European Studies, 2025)
The development of inclusive education in Uzbekistan has emerged as a critical component of the nation's educational reform efforts. This paper focuses on the inclusion of children with special educational needs (SEN) within inclusive environments, highlighting the role of the PRESETT (Promoting and Enhancing Special Education Teacher Training) program as a key initiative in fostering inclusive education. Through analyzing the progress of the program and the structural, policy, and practical adaptations made in the education system, this study demonstrates the importance of ensuring that children with SEN are fully integrated into general education settings. The paper also explores the challenges, successes, and the future potential for inclusive education in Uzbekistan. SEN stands for Special Educational Needs. It refers to the requirements of children who have learning difficulties or disabilities that make it harder for them to learn at the same pace or in the same way as other children. These needs can range from physical disabilities to cognitive, emotional, behavioral, or learning challenges, such as dyslexia, autism, Down syndrome, or speech and language disorders. In an educational context, when a child is identified as having SEN, schools and educators are typically expected to provide additional support or accommodations to help that child access the curriculum and succeed in their learning environment. This can include specialized teaching methods, tailored resources, or the use of assistive technology to ensure that children with SEN can participate fully in education alongside their peers.
Keywords: Inclusive education; special educational needs; Republic of Uzbekistan